2011
DOI: 10.1016/j.bbagrm.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the Snf2/Swi2 family Rad54 motor protein in homologous recombination

Abstract: Homologous recombination is a central pathway to maintain genomic stability and is involved in the repair of DNA damage and replication fork support, as well as accurate chromosome segregation during meiosis. Rad54 is a dsDNA-dependent ATPase of the Snf2/Swi2 family of SF2 helicases, although Rad54 lacks classical helicase activity and cannot carry out the strand displacement reactions typical for DNA helicases. Rad54 is a potent and processive motor protein that translocates on dsDNA, potentially executing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
141
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(154 citation statements)
references
References 170 publications
6
141
0
1
Order By: Relevance
“…The RAD51 protein binds to the ends of the DNA break to form RAD51 single-stranded DNA nucleoprotein filaments and is involved in strand invasion in HR. The RAD54 protein, a member of the SWI2/SNF2 family of ATP-dependent chromatin remodeling factors, plays diverse roles throughout HR processes, including stabilization of nucleoprotein filaments, facilitation of D-loop formation, and heteroduplex extension (Ceballos and Heyer, 2011;Knoll and Puchta, 2011). Our analyses show that expression of BRCA1, RAD51, and RAD54 is unaffected in nrp1-1 nrp2-1, excluding the hypothesis that NRPs regulate HR through transcriptional control of these key genes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The RAD51 protein binds to the ends of the DNA break to form RAD51 single-stranded DNA nucleoprotein filaments and is involved in strand invasion in HR. The RAD54 protein, a member of the SWI2/SNF2 family of ATP-dependent chromatin remodeling factors, plays diverse roles throughout HR processes, including stabilization of nucleoprotein filaments, facilitation of D-loop formation, and heteroduplex extension (Ceballos and Heyer, 2011;Knoll and Puchta, 2011). Our analyses show that expression of BRCA1, RAD51, and RAD54 is unaffected in nrp1-1 nrp2-1, excluding the hypothesis that NRPs regulate HR through transcriptional control of these key genes.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, DSB can cause a loss of nucleosomes within a few kilobases of the break (Tsukuda et al, 2005). HR is one of the two major pathways involved in repair of DSBs, but only a few factors involved in chromatin structure manipulation have been so far identified as playing a role in HR (Ransom et al, 2010;Avvakumov et al, 2011;Ceballos and Heyer, 2011;Lukas et al, 2011). HR events occur spontaneously and broadly throughout the genome; hence, it is difficult to monitor and detect HR products.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast Swi/Snf2-remodelling factors Rad54 and Tid1/Rdh54 specifically promote strand exchange reactions of Rad51 and Dmc1, respectively (Shinohara et al, 2000;Niu et al, 2009;Mazin et al, 2010;Ceballos and Heyer, 2011). Several members of this family can be found in the genome of Arabidopsis, but so far none of them has been found to be required for meiosis (P. Schlögelhofer, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Rad54B and Rad54 belong to a subfamily of doublestranded DNA-dependent ATPases referred to as the SWI2/SNF2 family, which is characterized by conserved helicase-like sequence motifs 5 . Although previous studies suggested that Rad54B plays roles in the HR and DNA repair processes [6][7][8][9] , biochemical analysis has shown that Rad54B is a less active DNA-dependent ATPase than Rad54 (ref.…”
mentioning
confidence: 99%